Standard dose and prolonged administration of azacitidine are associated with improved efficacy in a real‐world group of patients with myelodysplastic syndrome or low blast count acute myeloid leukemia. (21st June 2015) - Voso, Maria Teresa; Niscola, Pasquale; Piciocchi, Alfonso; Fianchi, Luana; Maurillo, Luca; Musto, Pellegrino; Pagano, Livio; Mansueto, Giovanna; Criscuolo, Marianna; Aloe‐Spiriti, Maria Antonietta; Buccisano, Francesco; Venditti, Adriano; et al.
Abstract: Objective: Azacitidine is the standard of care for higher‐risk myelodysplastic syndromes (MDS). We evaluated factors affecting the outcome of azacitidine treatment in 196 'real‐world' patients, retrospectively collected by two Italian cooperative groups. Methods: The study included 184 MDS and 12 low blast count acute myeloid leukemia (AML). Azacitidine was administered at the standard dose of 75 mg/m 2 /d for 7 d (SD) in 163 patients and 100 mg/d for 5–7 d in 33 patients. Results: After a median of 4.5 azacitidine cycles (range 7–15 cycles), 182 patients were evaluable for response. Nineteen percent achieved complete remission (CR), 17% partial remission (PR), and 21% hematological improvement (HI). The disease was stable or progressive in 29% and 14% of patients, respectively. The probability of response was significantly higher in patients who received the 75 mg/m 2 /7 d compared with 100 mg through 5–7 d dose (CR/PR/HI: 63 vs. 29%, P  = 0.0005). Median overall survival was 17.1 months. Low MDS‐CI and achievement of CR/PR/HI were significant predictors of survival in the multivariable analysis. Conclusions: Our data show that maximal azacitidine efficacy is associated with the standard dose and with prolonged treatment, beyond 4–6 cycles, with the goal of also improving the 'quality' of response. Lower MDS‐CI and IPSS‐R scores, hematologic response and disease stability, are associated with longer survival. The risk of febrile events is highest during the first treatment cycles and is associated with active disease.